Transcriptional upregulation of Bag3, a chaperone-assisted selective autophagy factor, in animal models of KY-deficient hereditary myopathy - Elliot J. Jokl; Gideon L. Hughes; Tobias Cracknell; Mary E. Pownall; Gonzalo Blanco (The Company of Biologists, 2018)
The importance of kyphoscoliosis peptidase (KY) in skeletal muscle physiology has recently been emphasised by the identification of novel human myopathies associated with KY deficiency. Neither the pathogenic mechanism of KY deficiency nor a specific role for KY in muscle function have been established. However, aberrant localisation of filamin C (FLNC) in muscle fibres has been shown in humans and mice with loss-of-function mutations in the KY gene. FLNC turnover has been proposed to be controlled by chaperone-assisted selective autophagy (CASA), a client-specific and tension-induced pathway that is required for muscle maintenance. Here, we have generated new C2C12 myoblast and zebrafish models of KY deficiency by CRISPR/Cas9 mutagenesis. To obtain insights into the pathogenic mechanism caused by KY deficiency, expression of the co-chaperone BAG3 and other CASA factors was analyzed in the cellular, zebrafish and ky/ky mouse models. Ky-deficient C2C12-derived clones show trends of higher transcription of CASA factors in differentiated myotubes. The ky-deficient zebrafish model (kyyo1/kyyo1) lacks overt signs of pathology, but shows significantly increased bag3 and flnca/b expression in embryos and adult muscle. Additionally, kyyo1/kyyo1 embryos challenged by swimming in viscous media show an inability to further increase expression of these factors in contrast with wild-type controls. The ky/ky mouse shows elevated expression of Bag3 in the non-pathological exterior digitorum longus (EDL) and evidence of impaired BAG3 turnover in the pathological soleus. Thus, upregulation of CASA factors appears to be an early and primary molecular hallmark of KY deficiency.